MOZAMBIQUE: A COMPARATIVE STUDY OF THE FOREIGN POLICY OF THE SAMORA MACHEL AND JOAQUIM CHISSANO GOVERNMENTS - Langa, Ercilio Neves Brandão (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The article analyses the Mozambican foreign policy in the Samora Machel and Joaquim Chissano Governments. It uses as a method Rosenau's comparative foreign policy analysis and theoretical contributions of Putnam's two-level game logic. The Samora government's foreign policy was one of regional liberation, antiapartheid and solidarity with oppressed states and peoples. Engaged in the Socialist Bloc, the Mozambican State faced internal and external constraints from the Cold War. Decisions were ideological, centred on the charismatic leader and President of the Republic. With his own agenda, Samora knew how to manage popular will with nationalizations, but Marxism-Leninism imposed military doctrine and diplomatic inflexibility. The Chissano Government's external relations were one of political-economic pragmatism, it sought new ideologies and opened itself up to dialogue and negotiations with unlikely partners. Considered a technocrat and an excellent diplomat, Chissano knew how to negotiate the end of the civil war, political-economic opening and help from the Western world. However, he made unpopular decisions: structural adjustment policies, transition from socialism to capitalism and changes to the Constitution. There were profound changes between the two Governments: from being an important regional political player and Soviet pawn, Mozambique became dependent on international aid and redefined its role, becoming a regional strategic economic partner, whose foreign policy agenda came to be influenced by international economic bodies.